2017
DOI: 10.1007/s13197-017-2740-3
|View full text |Cite
|
Sign up to set email alerts
|

Acorn (Quercus spp.) as a novel source of oleic acid and tocopherols for livestock and humans: discrimination of selected species from Mediterranean forest

Abstract: The aim of the present work was to characterization and compare acorns from selected spp. from the Mediterranean forest in Spain, namely, Portuguese oak (QF, Lam.), Cork oak (QS, L.), Pyrenean oak (QP, Wild), Kermes oak (QC, L.), Holm oak (QB, L. subsp. ballota [Desf.]). All physicochemical attributes varied significantly between species. Fat contents ranged from 1.30 to 4.70 g 100 g fresh matter. The most abundant fatty acids were oleic (62.44, 56.25, 57.46, 48.02, 65.83%), followed by linoleic (16.42, 20.73,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 29 publications
6
39
3
Order By: Relevance
“…A total of seven components were found to be the common for both extracts of QL. Previous studies on Quercus genus suggested that the species are rich in monounsaturated fatty acids, mostly oleic acid and also essential fatty acids such as linoleic (ω-6) and linolenic (ω-3) fatty acids, sesquiterpenes, terpenoids, flavonoids and phenolic acid [20,21,26] and in the present study same pattern of phytoconstituents were observed in the leaves and bark extracts of QL. Differences in quantity and quality of chemical components of any plant extract are highly influenced by several genetic and environmental factors, such as the genetic and seasonal variation, geographical origin, and the part of the plant used for the study, even agronomic conditions, developmental stage, time of collection, extraction method and solvent system [27].…”
Section: Resultssupporting
confidence: 84%
“…A total of seven components were found to be the common for both extracts of QL. Previous studies on Quercus genus suggested that the species are rich in monounsaturated fatty acids, mostly oleic acid and also essential fatty acids such as linoleic (ω-6) and linolenic (ω-3) fatty acids, sesquiterpenes, terpenoids, flavonoids and phenolic acid [20,21,26] and in the present study same pattern of phytoconstituents were observed in the leaves and bark extracts of QL. Differences in quantity and quality of chemical components of any plant extract are highly influenced by several genetic and environmental factors, such as the genetic and seasonal variation, geographical origin, and the part of the plant used for the study, even agronomic conditions, developmental stage, time of collection, extraction method and solvent system [27].…”
Section: Resultssupporting
confidence: 84%
“…Reported holm oak weight ranges from 1.2 to 6.5 g [10], lower than the ones determined in QR samples. As for QS acorns weight, mean values of 7.69 g have been reported [28], which also agrees with our results.…”
Section: Resultssupporting
confidence: 93%
“…Nutritional treatments are used to increase animal growth and manipulate the FA content improving the nutritional value of meat (Atti and Mahouachi, 2009;Ponnampalam et al, 2016). Oak acorn, due to its high content of C18:1, has an interesting FA profile (Cantos et al, 2003;Akcan et al, 2017) and so is largely used in pig production (Jurado et al, 2007;Pérez-Palacios, 2010). However, available data linking its effects on small ruminant growth and meat quality is very limited (Keddam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%